Systematic assessment of the Atelostomata (Spatangoida and Holasteroida; irregular echinoids) based on spine microstructure. (18th June 2015) - Schlüter, Nils; Wiese, Frank; Reich, Mike
<x xml:space="preserve">Abstract</x> Spines of irregular echinoids occur in very high abundance in each specimen, and display distinct architecture as a result of the specialized functions of the spines; however, studies on spine microstructure in atelostomate echinoids have rarely been carried out. Accordingly, little is known about their specific morphology. This work aims to elaborate differences in the spine morphology of selected Atelostomata (Spatangoida and Holasteroida) in detail, and to discuss spine microstructure for its potential systematic value. Based on 82 atelostomate species (56 spatangoids and 26 holasteroids), we show that the perforation pattern in the internal cylinder of the spine (helicoidal versus horizontal pattern) provides a safe distinction between the Spatangoida and Holasteroida. According to this character we discuss the geological history of atelostomate echinoids, in particular their migration into the deep sea, based on well‐preserved records of fossil spines. © 2015 The Linnean Society of London